PENGARUH FINANCIAL LEVERAGE DAN ARUS KAS TERHADAP FINANCIAL DISTRESS PERUSAHAAN SEKTOR INFRASTRUKTUR (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
This study was conducted to determine the effect of net income, operating cash flow and company size on dividend policy in manufacturing companies listed on the IDX for the period 2015 – 2019. Research methods and approaches use quantitative, with data collection techniques through the IDX official website. The sampling technique used purposive sampling technique, a sample of 8 companies multiplied by 5 years with a total sample of 40. The results of this study indicate that both net income, operating cash flow and company size partially have no effect on dividend policy in manufacturing companies listed on the IDX. the period 2015 – 2019 because the t-value of each independent variable is less than the t-table value (2.024). Meanwhile, simultaneously, net income, operating cash flow and company size have a positive and significant effect on dividend policy in manufacturing companies listed on the IDX for the period 2015 – 2019 with the calculated F value greater than the F table value (2.87). Keywords: Net Profit, Operating Cash Flow, Company Size, Dividend Policy